2023
DOI: 10.1021/acs.orglett.3c00950
|View full text |Cite
|
Sign up to set email alerts
|

Fluorosulfonylvinylation of Unactivated C(sp3)–H via Electron Donor–Acceptor Photoactivation

Abstract: An electron donor−acceptor (EDA) complex photoactivation strategy for radical fluorosulfonylation is disclosed for the first time. Simply upon blue light irradiation, the FSO 2 radical can be generated efficiently under catalyst-free, base-free, and additive-free conditions, which enables facile access to 6-keto alkenylsulfonyl fluorides from readily available propargyl alcohols and FSO 2 Cl. The 6-keto alkenylsulfonyl fluoride motif has been showcased as a versatile SuFEx hub with diverse follow-up derivatiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Our recent study disclosed a facile visible light-mediated method to access 6-keto alkenylsulfonyl fluorides (Scheme 15). 48 This was based on the formation of an electron donor–acceptor (EDA) complex between FSO 2 Cl and propargyl alcohol. This reaction is catalyst-free, base-free, and additive-free.…”
Section: Photochemical Synthesis Of Sulfonyl Fluoridesmentioning
confidence: 99%
“…Our recent study disclosed a facile visible light-mediated method to access 6-keto alkenylsulfonyl fluorides (Scheme 15). 48 This was based on the formation of an electron donor–acceptor (EDA) complex between FSO 2 Cl and propargyl alcohol. This reaction is catalyst-free, base-free, and additive-free.…”
Section: Photochemical Synthesis Of Sulfonyl Fluoridesmentioning
confidence: 99%
“…We initiated our studies by exploring the reaction of propargyl alcohol 1a , FSO 2 Cl ( 2 ), and aniline 4a . In our previous work, 13 we observed the formation of the intermediate 6-keto alkenylsulfonyl fluoride 3a in 99% yield, when the reaction was conducted at a concentration of 0.05 M with 2.5 equivalents of FSO 2 Cl ( 2 ). Thus, resulting 3a was then directly subjected to the following aza-Michael addition without purification.…”
mentioning
confidence: 87%
“…Inspired by the radical-mediated C(sp 3 )–H sulfonylvinylation reported by Zhu (Scheme 1C), 11 we recently employed a similar functional group migration strategy 12 for the synthesis of 6-keto alkenylsulfonyl fluorides. 13 As a continuation of this research program, we proposed that an C(sp 3 )–H fluorosulfonylvinylation/aza-Michael addition cascade would allow a novel approach to FSO 2 -THPs (Scheme 1D). The light irradiation of an electron donor–acceptor (EDA) complex 14 between propargyl alcohols 1 and FSO 2 Cl ( 2 ) would generate the fluorosulfonyl radical, which would undergo addition to the alkyne moiety of 1 .…”
mentioning
confidence: 99%
“…Similarly, the keto sulfonyl fluoride 2a can be readily substituted with morpholine and TMSN 3 , giving sulfonamide products in 91% ( 8a ) and 83% ( 9a ) yields, respectively (Scheme e,f) . Furthermore, product 2a can participate in Baeyer–Villiger oxidation to form ester 10a in 88% yield (Scheme g) …”
mentioning
confidence: 99%
“…25 Furthermore, product 2a can participate in Baeyer−Villiger oxidation to form ester 10a in 88% yield (Scheme 2g). 26 To gain insight into assumed photocatalytic C−C bond cleavage and fluorosulfonylation of cycloalkanols under blue LED irradiation, preliminary experimental mechanistic studies were performed (Figure 1). Initially, it was observed that the absence of the photocatalyst or light resulted in a significant decrease in yield (Figure 1a-1 and a-2).…”
mentioning
confidence: 99%